2020
DOI: 10.1038/s41598-020-75986-7
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric monitoring with the Chilean GPS eyeball during the South American total solar eclipse on 2nd July 2019

Abstract: The impact of total solar eclipse of July 2, 2019 on the Ionosphere is studied using 24 Chilean GPS stations north–south of the totality path. The total solar eclipse passed through Coquimbo region from ~ 16:38 CLT (~ 20:38 UTC) to ~ 16:40 CLT (~ 20:40 UTC) and maximum eclipse was observed ~ 16:39 CLT (~ 20:39 UTC). The total electron content (TEC) derived from GPS signals shows peculiar features. At the totality stations TEC variations are small (~ 0.39 TECu), but it shows significant decrease (maximum ~ 2.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Accordingly, the temperature profiles from both the TIMED‐SABER and ICON satellites suggest a reduction and enhancement in the lower and upper E regions respectively leading to the sudden inversions which can excite atmospheric gravity waves during the solar eclipse. To identify gravity wave activity along the eclipse path, usually, TEC observations across/along the eclipse path were investigated (Maurya et al., 2020; Nayak & Yiğit, 2018). We have examined 9 stations to see the gravity wave propagation in the TEC data.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the temperature profiles from both the TIMED‐SABER and ICON satellites suggest a reduction and enhancement in the lower and upper E regions respectively leading to the sudden inversions which can excite atmospheric gravity waves during the solar eclipse. To identify gravity wave activity along the eclipse path, usually, TEC observations across/along the eclipse path were investigated (Maurya et al., 2020; Nayak & Yiğit, 2018). We have examined 9 stations to see the gravity wave propagation in the TEC data.…”
Section: Discussionmentioning
confidence: 99%
“…Jonah et al (2020) suggests that it was the result of a perturbed ionospheric dynamo due to the eclipse. In addition, the SUPIM-INPE model used for the evaluation of the eclipse by Bravo et al (2020) did not considered the interaction with atmospheric gravity waves due to this eclipse observed by Maurya et al (2020) and Vargas et al (2022), and the generation of TIDs observed by Eisenbeis & Occhipinti (2021). Neither does the model consider the changes in the neutral composition, specifically in the O/N2 rate, recently observed by Aryal et al (2020a) from GOLD mission data during this event.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of multiple ground-based instruments along the continent (i.e., ionosonde stations, an Incoherent Scatter Radar, and GNSS receiver networks) and satellites (i.e., Swarm-A) are used to evaluate the accuracy of simulation results, providing a testbed scenario to determine the accuracy of the ionospheric prediction model under total eclipse conditions. In addition, the results of this evaluation are compared to the ionospheric response to the 2 July 2019, solar eclipse that occurred in the same geographical area (Bravo et al, 2020;Jonah et al, 2020;Maurya et al, 2020) and previous studies that evaluated the ionospheric response to the 14 December 2020, solar eclipse (e.g., Gómez, 2021;Meza et al, 2021;Shrivastava et al, 2021;de Haro Barbás et al, 2022;Resende et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the comprehensive studies have been conducted on the ionosphere interaction with Total/Annual solar eclipse effects, especially over the American and Indian equatorial low latitudes. In these studies, the relationship between ionospheric perturbations and physical mechanisms such as lunar tides, atmospheric gravity waves, electric field induced counter electrojets, total/vertical electron content, neutral winds and diffusion effects, has been examined in detail both during and before and after the solar eclipse [2,[30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%